A half-century of climate change in major agricultural regions: Trends, impacts, and surprises - David B. Lobell; Stefania Di Tommaso (Proceedings of the National Academy of Sciences, 2025)
Efforts to anticipate and adapt to future climate can benefit from historical experiences. We examine agroclimatic conditions over the past 50 y for five major crops around the world. Most regions experienced rapid warming relative to interannual variability, with 45% of summer and 32% of winter crop area warming by more than two SD (σ). Vapor pressure deficit (VPD), a key driver of plant water stress, also increased in most temperate regions but not in the tropics. Precipitation trends, while important in some locations, were generally below 1σ. Historical climate model simulations show that observed changes in crops’ climate would have been well predicted by models run with historical forcings, with two main surprises: i) models substantially overestimate the amount of warming and drying experienced by summer crops in North America, and ii) models underestimate the increase in VPD in most temperate cropping regions. Linking agroclimatic data to crop productivity, we estimate that climate trends have caused current global yields of wheat, maize, and barley to be 10, 4, and 13% lower than they would have otherwise been. These losses likely exceeded the benefits of CO 2 increases over the same period, whereas CO 2 benefits likely exceeded climate-related losses for soybean and rice. Aggregate global yield losses are very similar to what models would have predicted, with the two biases above largely offsetting each other. Climate model biases in reproducing VPD trends may partially explain the ineffectiveness of some adaptations predicted by modeling studies, such as farmer shifts to longer maturing varieties.